Impact of Ischemic Heart Disease on Serum Visfatin, Chemerin and High Sensitivity C - reactive protein in Iraqi Patients with T2 DM - Namir I. A. Haddad (Journal of Global Pharma Technology, 2016)
Objectives: Ischemic heart disease is a major cause of mortality among diabetic patients leading to about three-quarters of deaths among them. The study aimed to estimate serum visfatin, chemerin and hsCRP levels and other biochemical parameters in Iraqi diabetic patients with ischemic heart disease and compares it with newly diagnosed diabetic patients and control individuals. Methods: This study was carried out between October 2016 and March 2017 in Baghdad, Iraq, and involved 66 subject divided equally into three groups; 22 diabetic patient without IHD (P1), 22 diabetic patients with IHD (P2) and 22 non-diabetic healthy subjects (C). Serum visfatin, chemerin, hsCRP and other biochemical parameters were measured. Results: The results clarified that diabetic with IHD group had the highest levels of serum visfatin, chemerin and hsCRP in comparison with diabetic without IHD and control groups with means of (67.68±4.38 ng/ml, 59.73±9.42 ng/ml and 52.46±14 ng/ml respectively), (130.87±5.34 ng/ml, 127.85±4.30 ng/ml and 63.98±14.74 ng/ml respectively) and (8.37±1.03 mg/L, 7.54±1.19 mg/L and 4.55±2.31 mg/L respectively). These adipokines were found to be significantly correlated with some biochemical parameters. Conclusion: High levels of serum visfatin among diabetic patients indicate that there is an association between visfatin and hyperglycemia and it may be an independent risk factor for CHD. Although, both of the two inflammatory markers chemerin and hsCRP can be considered as markers of subclinical atherosclerosis and IHD, and they may be utilized for the early detection of macrovascular disease in type 2 diabetics.Keywords: CHD, Chemerin, Hscrp, IHD, T2DM, Visfatin.